Delegated Decree Authority In Contemporary South America - Kerry Mohan (My University, 2016)
International attention regarding executive decree authority within Latin America has significantly increased following Hugo Chávez' 2007 Enabling Law in Venezuela. This attention has largely been negative, as theinternational media has often vilified Chávez for promulgating decrees with the force of law. What the international media has continually failed to discuss, however, is that Chávez' form of decree authority, delegated decree authority (DDA), has been common throughout Venezuela's history, as well as that of most of South America. This article seeks to determine DDA's prevalence within South America, in particular within Venezuela and Ecuador, and determine whether DDA poses a threat to the rule of law within these nations. By focusing on Hugo Chávez ofVenezuela and Rafael Correa of Ecuador, we have a unique opportunity to see whether these charismatic leaders have used DDA to increase their law-making authority and consolidate powers within the Executive branch.